Adjuvant tamoxifen and exemestane in women with postmenopausal early breast cancer (TEAM): 10-year follow-up of a multicentre, open-label, randomised, phase 3 trial. Issue 9 (September 2017) - Derks, Marloes G M; Blok, Erik J; Seynaeve, Caroline; Nortier, Johan W R; Kranenbarg, Elma Meershoek-Klein; Liefers, Gerrit-Jan; Putter, Hein; Kroep, Judith R; Rea, Daniel; Hasenburg, Annette; Markopoulos, Christos; Paridaens, Robert; et al.
Summary: Background: After 5 years of median follow-up, the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial reported no difference in disease-free survival between exemestane monotherapy and a sequential scheme of tamoxifen followed by exemestane in postmenopausal patients with early-stage, hormone receptor-positive breast cancer. As recurrence risk in hormone receptor-positive breast cancer remains linear beyond 5 years after diagnosis, we analysed long-term follow-up outcomes of this trial. Methods: The TEAM trial, a multicentre, open-label, randomised, controlled, phase 3 trial, included postmenopausal patients with early-stage hormone receptor-positive breast cancer from nine countries. Patients were randomly allocated (1:1) by a computer-generated random permuted block method (block sizes 4–8) to either 5 years of oral exemestane monotherapy (25 mg once a day) or a sequential scheme of oral tamoxifen (20 mg once a day) followed by exemestane for a total duration of 5 years. After the publication of the IES trial, the protocol was amended (Dec 13, 2004). Patients assigned to tamoxifen were switched after 2·5–3·0 years to exemestane therapy for a total duration of 5·0 years of treatment. Randomisation was done centrally in each country. Long-term follow-up data for disease recurrence and survival was collected in six participating countries and analysed by intention to treat. The primary endpoint was disease-free survival at 10 years of follow-up. The trial is registered with ClinicalTrials.gov, numbers NCT00279448 and NCT00032136 ; with Netherlands Trial Register, number NTR 267; and the Ethics Commission Trial, number 27/2001. Findings: 6120 patients of the original 9776 patients in the TEAM trial were included in the current intention-to-treat analysis. Median follow-up was 9·8 years (IQR 8·0–10·3). During follow-up, 921 (30%) of 3075 patients in the exemestane group and 929 (31%) of 3045 patients in the sequential group had a disease-free survival event. Disease-free survival at 10 years was 67% (95% CI 65–69) for the exemestane group and 67% (65–69) for the sequential group (hazard ratio 0·96, 0·88–1·05; p=0·39). Interpretation: The long-term findings of the TEAM trial confirm that both exemestane alone and sequential treatment with tamoxifen followed by exemestane are reasonable options as adjuvant endocrine therapy in postmenopausal patients with hormone receptor-positive early breast cancer. These results suggest that the opportunity to individualise adjuvant endocrine strategy accordingly, based on patient preferences, comorbidities, and tolerability might be possible. Funding: Pfizer, Dutch Cancer Foundation.